Deficient Wnt Signaling and Synaptic Vulnerability in Alzheimer’s Disease: Emerging Roles for the LRP6 Receptor - Buechler, Johanna; Salinas, Patricia C. (Frontiers in Synaptic Neuroscience, 2018)
Synapse dysfunction and loss represent critical early events in the pathophysiology of Alzheimer’s disease (AD). While extensive research has elucidated the direct synaptotoxic effects of Amyloid-β (Aβ) oligomers, less is known about how signaling pathways at the synapse are affected by Aβ. A better understanding of the cellular and molecular mechanisms underlying synaptic vulnerability in AD is key to illuminating the determinants of AD susceptibility and will unveil novel therapeutic avenues. Canonical Wnt signaling through the Wnt co-receptor LRP6 has a critical role in maintaining the structural and functional integrity of synaptic connections in the adult brain. Accumulating evidence suggests that deficient Wnt signaling may contribute to AD pathology. In particular, LRP6 deficiency compromises synaptic function and stability, and contributes to Aß production and plaque formation. Here, we review the role of Wnt signaling for synaptic maintenance in the adult brain and the contribution of aberrant Wnt signaling to synaptic degeneration in AD. We place a focus on emerging evidence implicating the LRP6 receptor as an important modulator of AD risk and pathology.